Associações entre o diagnóstico prospectivo e retrospectivo do estado nutricional e a evolução clínica de pacientes internados em um hospital universitário - Sousa, Thaísa Alvim (2010)
Introduction: Protein Energy Malnutrition is one disease that contributes significantly to increased morbidity, causing impairment in response to treatments, inefficiency and delay in wound healing, decreased resistance of sutures, development of ulcers decubitus, glomerular filtration rate reduction, susceptibility to the development of infections and edema. The presence of these changes in malnourished patients is closely associated with increased cost and length of hospital stay and increased mortality. Hospitalized patients have high predisposition to development and / or exacerbation of protein-energy malnutrition due to metabolic stress inherent injury. Objectives: Identify associations between diagnosis of nutritional status by Subjective Global Assessment, frequency of complications, length of hospitalization, and clinical outcome of patients. Methods: To better evaluate the associations between nutritional status and outcome in patients at the Clinical Hospital of Federal University of Uberlândia, was developed a cross-sectional study with data collection from medical records of the file, about hospitalized patients between 01/07/2008 to 31/12/2008, and periodic follow-up of patients admitted during 01/09/2009 to 31/10/2009. Results: In the stage of retrospective data collection from medical records were included in the final analysis of 256 patients, 104 rated as "well nourished" (40.6%), 90 as "Moderate Malnutrition" (35.1%), and 62 as "Severe Malnutrition" (24.2%). Nutritional therapy was given to 15/152 (9.8%) malnourished and 11/104 "Well Nourished" (10.5%). Complications were identified in 50/152 malnourished (33.3%) and 17/104 "Well Nourished" (16.3%). Death occurred in 23/152 (15.3%) malnourished and 4/104 "Well Nourished" (3.8%). In only 18/152 charts the disease "Malnutrition" was included among the clinical diagnoses. In the stage of prospective data collection with tracking patients were evaluated at admission 73 patients as "well nourished" (66.9%), 28 patients as suffering from "malnutrition or Moderate Risk" (25.6%) and 8 patients as " Severe malnutrition (7.6%). During hospitalization, 11 patients developed or had worsening of malnutrition (10%). Nutritional therapy was administered to 22/36 "Malnourished" (61.1%). Complications occurred in 29/36 "Malnourished" (80.5%) and in 9/73 "Well Nourished" (12.3%). Deaths occurred in 12/36 "Malnourished" (33.3%) and 3/73 "Well Nourished" (4.1%). Discharge was given for 70/73 "Well Nourished" and 24/36 "Malnourished". The disease "Malnutrition" was included among the clinical diagnosis in only 5/36 records (13.9%). Conclusion: Malnutrition remains a actual problem, little recognized, valorized, and treated only sporadically, however have highly detrimental effect on the clinical course and prognosis of hospitalized patients.